Common Pool Resource Management in Soraha and Chhattis Farmer Managed Irrigation Systems of Rupandehi District - Gewali, B. R. (Economic Journal of Nepal, 2014)
Common pool resource and its management is a popular subject today. Soraha and Chhattis Mauja Farmer Managed Irrigation Systems of Rupandehi are managing common pool resources successfully. The organization and management evolved by the local people to utilize the natural resource for the agriculture production is very important to apply in the management of other public goods. These irrigation systems are farmer managed and running successfully for more than hundred years. These are based on traditional skill and technique with the use of local labour and raw materials. The basic characteristic of Soraha and Chhattis Farmer Managed Irrigation Systems (S-CFMISs) is Kulara entitlement. This entitlement balances the rights and duties of share holders within the system. This unique technique was developed by the local farmers with their own skill. These low cost irrigation systems are useful to increase agricultural production. But with the pace of urbanization these systems are facing the problems like labour deficiency and contraction of command area. The Economic Journal of Nepal, Vol. 34, No. 1, January - March 2011 (Issue N0. 133) Uploaded date: 3/27/2014